2020
DOI: 10.1097/md.0000000000022120
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography of the saphenous nerve

Abstract: The purpose of this study is to study sonoelastographic features of the saphenous nerve. The study included 72 saphenous nerves in 36 healthy subjects. High resolution ultrasound and Shearwave elastography were used to evaluate the saphenous nerve. Cross sectional area (CSA) and stiffness were measured. The mean CSA of the saphenous nerve was 5.7 mm 2 . The mean shear elastic modulus of the saphenous nerve in the short axis was 29.5 kPa. The mean shear elastic modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Despite its broad utility, the scale of a targeted nerve should be carefully considered when interpreting SWE outcomes. In one study, the mean stiffness of the saphenous nerve was found to be very similar in the short and long axes [66], a finding inconsistent with multiple other investigations showing a higher shear wave speed in the longitudinal plane [1,67]. It is likely that reliable elasticity data could not be acquired in the transverse plane of the nerves [51], potentially due to the similar scale of nerve diameter and the wavelength of the shear waves and a higher signal from wave reflections at the fiber bundles, apparent in the nerve's transverse plane [1,67].…”
Section: Considerations For Evaluating Peripheral Nerves With Swementioning
confidence: 99%
“…Despite its broad utility, the scale of a targeted nerve should be carefully considered when interpreting SWE outcomes. In one study, the mean stiffness of the saphenous nerve was found to be very similar in the short and long axes [66], a finding inconsistent with multiple other investigations showing a higher shear wave speed in the longitudinal plane [1,67]. It is likely that reliable elasticity data could not be acquired in the transverse plane of the nerves [51], potentially due to the similar scale of nerve diameter and the wavelength of the shear waves and a higher signal from wave reflections at the fiber bundles, apparent in the nerve's transverse plane [1,67].…”
Section: Considerations For Evaluating Peripheral Nerves With Swementioning
confidence: 99%